2021
DOI: 10.1038/s41598-021-99524-1
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A loss-of-function predicts immunotherapy resistance in non-small cell lung cancer

Abstract: Immune checkpoint blockade (ICB) improves outcomes in non-small cell lung cancer (NSCLC) though most patients progress. There are limited data regarding molecular predictors of progression. In particular, there is controversy regarding the role of CDKN2A loss-of-function (LOF) in ICB resistance. We analyzed 139 consecutive patients with advanced NSCLC who underwent NGS prior to ICB initiation to explore the association of CDKN2A LOF with clinical outcomes. 73% were PD-L1 positive (≥ 1%). 48% exhibited high TMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…Our findings did not support a link with BAP1 loss and the immune ‘hot’ phenotype in MPM. Compared to peritoneal mesothelioma, MPM harbour more frequent loss of CDKN2A , and loss of CDKN2A has been linked to resistance to immunotherapy in non-small cell lung cancer [ 77 ]. Therefore, the CDKN2A loss may contribute to the lack of association with the immune ‘hot’ phenotype in MPM.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings did not support a link with BAP1 loss and the immune ‘hot’ phenotype in MPM. Compared to peritoneal mesothelioma, MPM harbour more frequent loss of CDKN2A , and loss of CDKN2A has been linked to resistance to immunotherapy in non-small cell lung cancer [ 77 ]. Therefore, the CDKN2A loss may contribute to the lack of association with the immune ‘hot’ phenotype in MPM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CDKN2A mutations which were identified in 6.9% of samples were recently associated with increased resistance to immune checkpoint inhibitors. A study by Gutiontov et al showed that NSCLC harboring a CDKN2A loss-of-function mutation had a twofold increase in immunotherapy resistance, irrespective of PD-L1 expression, and a poorer clinical outcome [ 23 ]. In addition, DDR2 gene mutations were associated with 4.5% of our cases; DDR2-mutated LUADs showed sensitivity to dasatinib, supporting a possible role for combined chemotherapy in these patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among challenges faced by the future of cancer immunotherapy, is understanding cancer-intrinsic factors regulating TME leading to immune evasion (Wellenstein and de Visser, 2018;Hegde and Chen, 2020). Recent studies found that genomic CDKN2A loss-of-function is associated with worse clinical outcome in patients treated with cancer immunotherapy in multiple cancer types (Adib et al, 2021;Gutiontov et al, 2021;Zhu et al, 2021). The reduced benefit of cancer immunotherapy can be attributed to altered tumorimmune microenvironment and compromised immune cell functions.…”
Section: Justify the Value Of Arf-targeting Cancer Therapiesmentioning
confidence: 99%